A Sensitive High‐Throughput Screening Method for Identifying Small Molecule Stimulators of the Core Particle of the Proteasome. Issue 4 (4th October 2018) - Coleman, Rachel A.; Trader, Darci J.
Abstract: Fluorescence resonance energy transfer (FRET) technology is a useful tool to monitor protein interactions as well as protease activity. We have recently reported a biochemical assay utilizing a FRET reporter peptide to monitor the activity of the 20S catalytic particle (20S CP) of the proteasome. This assay is designed specifically to have increased sensitivity to identify stimulators of the 20S CP, which may hold therapeutic potential to treat protein‐accumulation diseases. The protocol described here details the necessary steps in synthesizing the FRET reporter peptide and performing the FRET assay with the 20S CP. © 2018 by John Wiley & Sons, Inc.